Effect of omega-3 fatty acids from ahestnuts on the blood lipid values of men and women from UPeU between 20 and 50 years of age during the year 2007 - María Collantes Cossío (2019)
Objective: Measure the effect of Omega-3 fatty acid consumption from chestnuts on the blood lipid values ofmen and women from the Universidad Peruana Union between 20 and 50 years of age.Method: The study was experimental, analytical and prospective, with two independent groups. The researchentitled “Effect of omega-3 fatty acids from chestnuts on the blood lipid values of men and women from UPeUbetween 20 and 50 years of age,” was carried out during the months of May and October of 2007. It was conformedof two groups: experimental group and control group with 39 and 18 participants respectively.From the experimental group, three blood samples were drawn to identify the lipid profile and from the controlgroup only two blood samples were drawn.The diet of the experimental group was complemented with the daily consumption of 55 grams of chestnuts,without interfering with the rest of the nutritional habits and lifestyle. With the intention of discovering the effectof Omega-3 fatty acid consumption from chestnuts on the lipid profile. The quantity of chestnuts consumed dailyconsisted of 55 grams which contributed 4.2 grams of omega-3.Results: This study was made up of two groups: experimental and control with 39 and 18 participants respectively. It can be said concerning the results that the consumption of chestnuts significantly reduced the levels ofcholesterol and triglycerides. The total cholesterol was reduced from 180,77 mg/dl. to 167,29 mg/dl. (equiv. = 0,01)and the triglyceride levels were reduced from 131,41 mg/dl. to 111,82 mg/dl. (equiv. = 0,02).The consumption of chestnuts increased the levels of HDL cholesterol from 37,67 mg/dl. to 38,13 mg/dl.,which was not significant (equiv. = 0,534), however it can be deduced that there is a tendency to maintain thelevels of HDL cholesterol. Likewise, we can conclude about the levels of LDL cholesterol, that the consumption of chestnuts achieved reductions in LDL cholesterol levels from 115,34 mg/dl. to 106,67 mg/dl., but itwas not significant (equiv. = 0,076).Conclusion: Therefore, for finalizing this research we can recommend the regular consumption of omega-3through chestnuts as it can prevent cardiovascular diseases by preventing increases in blood lipids. However, furtherresearch is recommended into the other nutritional properties of the chestnut, such as its fiber content which is another hypolipemiant element, likewise relate the consumption of chestnuts with other factors such as diet, physicalactivity, etc.And lastly, to make known that the consumption of chestnuts has health benefits for people, to such an extentthat it could be a product to be promoted and made accessible for consumption by the Peruvian population as ournational market for chestnuts is quite low. The national market is below 1% of the total production, as nearly theentirety is for exportation to international markets, principally in Europe and the United States.In this way, it would be an initiative that would not only influence improvements in cultivation and production,but also its commercialization. Therefore, it could improve and increase the economic revenue of the country.